The Role of Family as A Caregiver in Caring for Family Members that are Suffering from Pulmonary Tuberculosis - Beti Kristinawati; Annisa Muryadewi; Ana Dwi Irianti (Universitas Airlangga, 2019)
Introduction: Families have an important role in the successful treatment of people with pulmonary tuberculosis. The purpose of this study was to obtain an overview of the role of the family as a caregiver in caring for family members suffering from pulmonary tuberculosis.Methods: The phenomenological qualitative design was chosen to obtain in-depth information by interviewing thirteen family members who cared for pulmonary tuberculosis patients determined through a purposive technique. Results: The content of Collaizi's analysis produced five themes, namely: 1) Nonpharmacological therapy is given by the family to treat symptomatic pulmonary tuberculosis 2) Efforts to cut transmission was carried out by the family to prevent transmission of disease, 3) Nutrition support provided by families in treating patients, 4) Instrumental support given by families in caring for pulmonary tuberculosis patients, 5) Emotional support given by families in treating pulmonary tuberculosis sufferers.Conclusion: The family provides physical and psychological care to support the successful treatment of pulmonary tuberculosis. A program is recommended to increase family knowledge in caring for family members suffering from pulmonary tuberculosis. Words are sorted alphabetically.